مبدأ الشفافية في إبرام الصفقات العمومية في ظل قانون 23/12 - مروه بديده (جامعة الوادي University of El Oued, 2025)
يعتبر قانون 23/12 أحد الأسس الجوهرية لضمان النزاهة وحسن إستخدام المال العام،وقد سعت إلي إبراز كيفية تكريس هذا المبدأ في التشريع الجزائري،ومدى جدية المشرع في تفعيله من خلال وضع آليات قانونية فعالة وإطار تنظيمي دقيق وصارم،وتهدف الدراسة إلي توضيح أهمية مبدأ الشفافية كوسيلة لتحقيق الحوكمة الرشيدة وترسيخ الثقة بين المواطن والإدارة،وخاصة في مجال الصفقات العمومية الذي يعد من أكثر المجالات عرضة للفساد والتجاوزات،كما تسعى إلي تقييم مدى نجاعة الضمانات الموضوعية لضمان احترام هذا المبدأ،سواء من حيث النصوص القانونية أو من حيث أدوات الرقابة والتتبع الإداري والقضائي،ونستنتج بأن المشرع الجزائري أبدي اهتماما متزايدا بتعزيز مبدأ الشفافية من خلال القانون رقم 23/12،غير أن فعالية هذا المبدأ تبقي رهينة بالتطبيق الفعلي له علي أرض الواقع،وهو ما يتطلب وجود إرادة سياسية قوية،وتفعيل صارم لآليات الرقابة حفاظا علي المال العام وتحقيقا لمبادئ العدالة والشفافية This dissertation examines the principle of transparency in the awarding of public contracts under law12 recogniwing it as a fundamental guarantee for integrity and the sound management of public funds it aims to highlight how the Algerian legislator has enshrined this principle in national legislqtion and the extent to which it is supported by effective legal mechanisms and a strict regulatory framework the study underscores the importace of transparency as a tool for promoting good governance and restoring public trust in government institutions particularly in the sensitive field of public procurement which remains highly vulnerable to corruption and misconduct it also assesses the effectiveness of the safeguards in place to ensure adherence to this principle both in legal provisons and through administrative and judicial oversight the research concludes that while the Algerian legislator has shwn increased commitment to enhancing transparency through law 12/23 the true measure of success lies in its concrete application this requires a strong political will and the rigorous activeation of oversight mechanisms to protect public resources and uphold principles of jusources and uphold principles of justice and transparency
قانون إداري
Keywords: مبدأ الشفافية - الصفقات العمومية - قانون 23/12; Principle of transparency-public transactions-law 23/12